TINJAUAN HUKUM TERHADAP PENETAPAN KELOMPOK KRIMINAL BERSENJATA (KKB) PAPUA SEBAGAI KELOMPOK TERORIS DALAM PERSPEKTIF HUKUM PIDANA NASIONAL (Jurnal Hukum Mimbar Justitia, 2021)
The escalation of conflict in Papua due to the actions of the Papua Armed Criminal Group (KKB), which is a pro-independence group for the land of Papua, has pushed the government to take firmer action by establishing the KKB as a theoretical group. Of course this brings pros and cons in various circles. This research is intended to examine whether the determination of the KKB as a terrorism group is objective and appropriate according to the criminal law, especially when examined from the Terrorism Law. The research method uses the normative juridical method. Based on the research results, it is known that the government has rightly designated the KKB as a terrorism group because the actions carried out by the KKB indicate the fulfillment of the elements of the offense of terrorism in the Terrorism Law. Furthermore, the government can enforce criminal law against KKB according to the Terrorism Law through authorized institutions as in the Integrated Criminal Justice System. In addition, the TNI can also be involved on a limited basis in the title of the Military Operation Other Than War (OMSP) pattern.Keywords: Criminal, Government, KKB papua, Terrorism.